Sex differences in neural processing of speech in neonates. (December 2022) - Alexopoulos, Johanna; Giordano, Vito; Doering, Stephan; Seidl, Rainer; Benavides-Varela, Silvia; Russwurm, Magdalena; Greenwood, Stephanie; Berger, Angelika; Bartha-Doering, Lisa
Abstract: The large majority of studies shows that girls develop their language skills faster than boys in the first few years of life. Are girls born with this advantage in language development? The present study used fNIRS in neonates to investigate sex differences in neural processing of speech within the first days of life. We found that speech stimuli elicited significantly more brain activity than non-speech stimuli in both groups of male and female neonates. However, whereas girls showed significant HbO changes to speech stimuli only within the left hemisphere, boys exhibited simultaneous neural activations in both hemispheres, with a larger and more significant fronto-temporal cluster in the right hemisphere. Furthermore, in boys, the variation in time-to-peak latencies was considerably greater than in girls. These findings suggest an earlier maturation of language-related brain areas in girls and highlight the importance of sex-specific investigations of neural language networks in infants.